Chapter 21: Amidst the flyway: co-designing accommodation fields for the barnacle goose in south-eastern Finland - Hiedanpää, Juha (Edward Elgar Publishing, 2023)
The barnacle goose (Branta leucopsis) is strictly protected under the Finnish national and EU legislation. The protection has succeeded: the size of the Russia/Germany and Netherlands population has increased from 20 000 individuals to 1.4 million individuals in 40 years (1980-2020). Some 500 000-800 000 individuals of this population nowadays stopover in Finland during their spring and autumn migrations between their breeding grounds in the Russian Arctic and wintering grounds along the North Sea coast. To the frustration of the farmers, resting and feeding in the agricultural areas cause major damage, resulting in a human-wildlife conflict - the alleviation of which calls for a wide range of approaches. The reimbursement for farmers has dramatically increased in ten years, with €3 million paid by the Finnish government in 2020. In collaboration with local farmers and regional and national environmental administration, we co-designed and experimentally tested accommodation fields for geese using a rights-based framework. On these fields, geese are allowed to forage and rest without disturbance, while geese are repelled from neighbouring fields, dedicated to regular farming. In this chapter, we explain our transdisciplinary findings about the institutional and natural conditions of these accommodation fields.